Sliding wear behaviour of oriented ultrahigh molecular weight polyethylene. Issue 6 (4th December 2012) - Eddoumy, Fatima; Addiego, Frédéric; Dhieb, Houcine; Célis, Jean‐Pierre; Muller, René; Toniazzo, Valérie; Ruch, David
Abstract The impact of processing‐induced chain orientation on the sliding wear behaviour of ultrahigh molecular weight polyethylene (UHMWPE) was investigated. The orientation of the molecular network of UHMWPE was done by means of uniaxial tension up to different residual strains. We found that high residual strain levels (higher than 0.45) enabled the sliding dissipated energy of UHMWPE to be decreased in dry conditions. In particular, oriented UHMWPE with a residual strain of 0.85 exhibited, at 500 000 sliding cycles in dry conditions, a decrease in volumetric wear loss by a factor of 3.3 and 19.4 compared with the reference UHMWPE tested in directions parallel and perpendicular to the chain direction, respectively. It is argued that oriented UHMWPE exhibits less adhesion during interfacial wear than the reference material, and hence orientation of UHMWPE bulk may be an alternative treatment to crosslinking for dry sliding conditions. In the case of sliding testing conducted in Ringer's solution, the benefit of the initial chain orientation was quite weak due to a lubrication effect of the solution that markedly limited the effect of chain orientation on the sliding behaviour.